The NIH Countermeasures Against Chemical Threats Program: overview and special challenges - Jett, David A. (Ann N Y Acad Sci, 2016)
Intentional exposures to toxic chemicals can stem from terrorist attacks, such as the release of sarin in the Tokyo subway system in 1995, as well as from toxic industrial accidents that are much more common. Developing effective medical interventions is a critical component of the overall strategy to overcome the challenges of chemical emergencies. These challenges include the rapid and lethal mode of action of many toxic chemicals that require equally fast-acting therapies, the large number of chemicals that are considered threats, and the diverse demographics and vulnerabilities of those who may be affected. In addition, there may be long-term deleterious effects in survivors of a chemical exposure. Several U.S. federal agencies are invested in efforts to improve preparedness and response capabilities during and after chemical emergencies. For example, the National Institutes of Health (NIH) Countermeasures Against Chemical Threats (CounterACT) Program supports investigators who are developing therapeutics to reduce mortality and morbidity from chemical exposures. The program awards grants to individual laboratories and includes contract resource facilities and interagency agreements with Department of Defense laboratories. The range of high-quality research within the NIH CounterACT Program network will be discussed.